The Effects of Applied Grip Force, Frequency and Duration on Ratings of Perceived Exertion - (:unkn) unknown (My University, 2015)
This study investigates the interactions of various combinations of frequency and duration that result in the same duty cycle at a given applied grip force (measured in % maximum voluntary contraction (MVC)) to determine their relative effect on perceived exertion. Eight female subjects (median age 20.5 years) performed 27 randomized trials containing combinations of dynamic grips, performing each combination twice. Each session contained three 25 minute trials, with a minimum of 12 minutes of rest between trials. The design used a 3x3x3 factorial protocol: i) 3 grip forces (10%, 25%, 40%) ii) 3 duty cycles (25%, 50%, 75%) iii) 3 durations (1, 4, 7 seconds). Subjects were asked to rate their level of perceived exertion every 2.5 minutes, throughout the entire 25 minute trial (or until it became too difficult to continue) using the Borg CR-10 scale (Borg, 1998). Although force seems to have the strongest effect on increased Borg CR-10 ratings (of all the tested factors), it was only significant as a main effect in a model that tested %MVC * Duty Cycle. The interaction of factors was statistically significant (p ≤ 0.01) for both models tested: i) % MVC * Duty Cycle ii) % MVC * Frequency * Duration. The model which separated frequency and duration was a slightly better fit, based on a likelihood ratio test. However, from a practical standpoint, it appears that for the tested parameters, duty cycle alone is a sufficient measure of exertion. This study also found that combinations combining high force and high duty cycle were the most difficult for subjects. Combinations of lower force and modest duty cycles (containing modest frequencies) were the easiest for subjects to sustain. Future studies should look at a broader range of durations and higher forces to further define acceptable (i.e., sustainable, safe) repetitive dynamic grip combinations.
Keywords: Duration; Duty Cycle; Frequency; Grip Force; Perceived Exertion